Effects of plant growth regulator from seaweed extracts on expression of genes regulating the oil and related metabolites productions in oil palm (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kresnawaty I, Santoso D,Hudiyono S. 2022. Effects of plant growth regulator from seaweed extracts on expression of genes regulating the oil and related metabolites productions in oil palm. Biodiversitas 23: 793-800. Plant growth regulators (PGRs) have been used in agricultural practicesto regulate various processes, such as germination, vegetative growth, reproduction, maturation, leaf senescence and post-harvest. Seaweed extract as natural PGRs source containsauxin, cytokines, and gibberellins. Although PGRs have been used for decades, the effects of these compounds on the production of secondary metabolites, proteins and related gene-expressionare not yetwell knownin some perennial crops.To study those,treatments consist of trunk injection of oil palm trees with biostimulant that contain PGRs from seaweed extract. Effects of treatments compared were biostimulant (B), biostimulant with activator for oil accumulation (BA) and control (C). The results indicated that the biostimulant treatments affected ACCase Biotin Carboxylase and HMG-CoA genes expression ratio andwere maximum at4 weeks after treatments (WAT) for biostimulant with activators treatments and 8 WAT for biostimulants without activator. Effect of biostimulants treatments in inducing the gene expression was not significant after 8 WAT. Moreover samples with addition biostimulant in 1 and 7 had the highest values ??ofthe gibberellin (GID) gene expression. Oil accumulation showed increase in 4 WAT dan had optimum level in 8 WATbecause of activators addition, especially increased of palmitic and linoleic acid.